If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.59x+48=1.19x
We move all terms to the left:
0.59x+48-(1.19x)=0
We add all the numbers together, and all the variables
0.59x-(+1.19x)+48=0
We get rid of parentheses
0.59x-1.19x+48=0
We add all the numbers together, and all the variables
-0.6x+48=0
We move all terms containing x to the left, all other terms to the right
-0.6x=-48
x=-48/-0.6
x=+80
| -9.3=s+1.7 | | 1x+15=4x-3 | | 6(c-54)=2 | | 3x-11=66 | | x+6=2(2+14) | | x+6=6(x+14) | | x+6=(x+14) | | 6x-3x+3=3x-3x+15 | | x-4=x-10 | | -2(5+6n)6(8-2n)=180 | | 81x+18=-30 | | 10^2n-5=500 | | 2x-5+2x-5+2x-5=180 | | 6x-4=13x-36 | | 57.6=6(m+3.4) | | 2,709=43(p+15) | | 4x-4+4x-4+4x-4=180 | | 243x+240=80-32x | | -2x-6=(3/2)(-2x-2) | | -5x-36=-5(x=8)=4 | | 4=25x=15x+6 | | 5/6(12p+6)=-13p+4 | | 2x-6=(x-1) | | 6(x-6)+10=6x-26 | | 8x-20=12+4x | | -18+x=4 | | 8+7r=2+5 | | 4x+3.5=4.5 | | -5(3x-9)=2(x-5)-75 | | 2x+6=7+8x | | 3+4x=3(-x+9)38 | | 2x+6=7-3+8x |